Acehnese Cultural Context in Islamic State Higher Education Institutions' Management of International Internships (Malaysia & Thailand) - Hasnadi, Hasnadi; Hanif, Hanif; Al Marbawi, Usman; Srisamout, Bancharat; Rahman, Fatkur; Rahim, Reynaldi Aulia (Idarah (Jurnal Pendidikan dan Kependidikan), 2025)
The purpose of this study is to analyze and describe the planning, actuating and evaluating faced by students in participating in international internship program activities at Islamic universities in Aceh. This research is a qualitative study. The subjects of this study include students, the Dean of the Faculty of Tarbiyah and Teacher Training, supervising lecturers, as well as principals and teachers at schools in Malaysia and Thailand. The research was conducted at three state campuses in Aceh, namely Ar-Raniry State Islamic University, State Islamic Institute of Lhokseumawe, and Teungku Dirundeng Meulaboh State Islamic College, which have carried out international internship activities in the last two years. Data collection was carried out through observation, interviews, and document studies. Data analysis involved data reduction, data display, verification, and conclusion. The results of the study concluded that state Islamic universities in Aceh have conducted international teaching internship program in Malaysia and Thailand, each with its private regulations regarding implementation. The stages of these international teaching internship generally consist of planning, implementation, and post-implementation. Higher education management has a strategic role in improving the competence of prospective teachers through international internship programs that are well managed, collaborative and without eliminating local values and Acehnese culture. The pedagogical, professional, social competence and understanding of intercultural differences of prospective teachers can be improved if the international internship program is managed with an integrated approach, starting from planning, implementation, and evaluation involving various stakeholders.